Improving The Ability to Write Official Letters Using “Sibomber” Method Assisted by Interactive Quizzes for VIIth Grade Students at SMPN 44 Jakarta - Karen Begaratri; Kusmayati, Nurita Bayu; Puspitaningrum, Ririn (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study aims to describe the improvement of official letter writing skills using the Sibomber method assisted by interactive quizzes. The Sibomber method stands for Prepare a study plan, Guided learning, Optimal-complete, Independent, Practice, Evaluate, and Reflect. This method aims to develop students' ability to receive information from their peers individually. The interactive quiz used is kahoot! Action class research conducted consisted of 4 stages, namely planning, action, observation, and reflection. The subjects of this research were class VII-H students of SMP Negeri 44 Jakarta. There were 36 students consisting of 20 boys and 16 girls. In collecting research data, interview sheets, questionnaires, field notes, and documentation were used. Actions carried out in two cycles. In the first cycle, the average value was 69.17, and in the second cycle it was 80.56, so that there was an increase in the value of 11.39.